Resilience of an African giant : boosting growth and development in the Democratic Republic of Congo - Herderschee, Han.; Kaiser, Kai-Alexander.; Mukoko Samba, Daniel; World Bank. (Washington, D.C. : World Bank, 2012)
The development of an effective state, a reliable infrastructure, and a dynamic private sector has long been hampered by political economy obstacles in the Democratic Republic of Congo. Resilience of an African Giant identifies these obstacles, which prevent the country from realizing its economic potential, and outlines how they can be - and in some cases have been - overcome.
Includes bibliographical references and index.
oif 18/07/2018
Loans
Keywords: Economic development; Congo (Democratic Republic); Congo (Democratic Republic)